Washington, a chronological & documentary history, 1790-1970 - 1934-; Furer, Howard B. (Dobbs Ferry, N.Y. : Oceana Publications, 1975)
Presents a chronology of important events in the history of Washington, D.C., accompanied by pertinent documents.
Includes index.
Bibliography: p. 143-152.
Keywords: Washington (D.C.) -- History -- Chronology; Washington (D.C.) -- History -- Sources; Washington (D.C.) -- History